Effects of porosity and strain rate on the uniaxial compressive response of ice-templated sintered macroporous alumina. (1st May 2018) - Banda, Mahesh; Ghosh, Dipankar
Abstract: We investigated and thoroughly analyzed compressive response of ice-templated ceramics in quasistatic and dynamic regimes of strain rate. In the high pore volume regime, sintered scaffolds exhibited highly lamellar pore morphology and pore architecture transitioned to dendritic with the decreasing pore volume. Mechanical property measurements in the quasistatic regime of strain rate revealed that with increasing density, compressive response transitioned from a damageable, cellular-like failure to a brittle-like failure. We rationalized the measured results in terms of the propensity of the lamella walls to undergo buckling. Our conjecture is that in the high pore volume regime, lamella walls of the scaffolds are prone to buckling-induced elastic instability, which leads to a compressive response that manifests a gradual decrease of stress beyond peak stress. In contrast, we suggest that in the low pore volume regime thick lamella walls and extensive transverse bridging exhibit marked resistance to buckling-induced instability and scaffolds undergo a global failure, which is manifested in the measured quasistatic compressive response as a sharp drop of stress beyond peak stress. Dynamic compressive response of the scaffolds exhibited measurable differences relative to the quasistatic compressive response. Scaffolds exhibited a relatively gradual decrease of dynamic compressive stress beyond peak stress, and an overall improvement of compressive response and energy absorption capacity was measured under the dynamic loading conditions. We rationalized the measured differences in between the strain rate regimes in terms of the micro-inertia and other effects. This study is of critical significance for applications of ice-templated structures in dynamic environments. Graphical abstract: Image 1